2019
DOI: 10.1080/19420862.2019.1654303
|View full text |Cite
|
Sign up to set email alerts
|

Durable blockade of PD-1 signaling links preclinical efficacy of sintilimab to its clinical benefit

Abstract: Blockade of immune checkpoint pathways by programmed cell death protein 1 (PD-1) antibodies has demonstrated broad clinical efficacy against a variety of malignancies. Sintilimab, a highly selective, fully human monoclonal antibody (mAb), blocks the interaction of PD-1 and its ligands and has demonstrated clinical benefit in various clinical studies. Here, we evaluated the affinity of sintilimab to human PD-1 by surface plasmon resonance and mesoscale discovery and evaluated PD-1 receptor occupancy and anti-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 32 publications
1
103
0
Order By: Relevance
“…However, immunotherapy combined with anti-angiogenesis therapy presented a synergistic effect on the mechanism of action [23,46], which was proved by a trial of IMbrave 150 in unresectable HCC patients [23]. Strategies that combine other types of immunomodulators, chemotherapy, and molecular targeted treatments either in vivo or in vitro are ongoing [5].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…However, immunotherapy combined with anti-angiogenesis therapy presented a synergistic effect on the mechanism of action [23,46], which was proved by a trial of IMbrave 150 in unresectable HCC patients [23]. Strategies that combine other types of immunomodulators, chemotherapy, and molecular targeted treatments either in vivo or in vitro are ongoing [5].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Compared with pembrolizumab or nivolumab, sintilimab has a different binding site and potentially greater affinity against PD-1 as per the preclinical data. 11 In a phase 1b study, sintilimab plus pemetrexed and platinum has been found to have tolerable safety profile and promising efficacy in previously untreated patients with nonsquamous NSCLC, with an objective response rate (ORR) of 68.4% and a median progression-free survival (PFS) of 11.4 months. 12 In this randomized, doubleblind, phase 3 study (ORIENT-11), we compared the combination of pemetrexed and platinum plus either sintilimab or a placebo in Chinese patients with locally advanced or metastatic nonsquamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…It is safe to hypothesize that anti-PD-1 antibodies in combination with chemotherapy may further improve the clinical outcomes of patients with advanced GC. Sintilimab is a highly selective, monoclonal IgG4 antibody that inhibits interactions between PD-1 and its ligands, with strong anti-tumor response [ 23 ]. A phase 1a study for dose escalation, has demonstrated the tolerance and pharmacological activity of sintilimab in patients with advanced-stage solid tumors, but there is limited evidence for the efficacy of antibodies against PD-1 plus chemotherapy in Chinese G/GEJ adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%